Family size differentials in five selected areas in the Philippines - Osteria, Trinidad Sarao 1944-
This study of family size differentials was based on the fertility surveys conducted by the U.P. Statistical Center, Institute of Hygiene, and the Population Institute from the year 1963 to 1966. Information was obtained on the marital history, fertility performance, and socio-economic characteristics of the married woman who was, in most cases, the wife of the household head. The objectives of the study were: (1) the determination of variation in family size by age at marriage, education of the people, occupation of the husband, employment status of the wife, annual household income, and farm tenancy status; and (2) comparison of fertility levels based on these socio-economic characteristics among municipalities.